Pathophysiological mechanisms of cognitive impairment and neurodegeneration bt Toxoplasma gondii infection (2020)
Toxoplasma gondii is an obligate intracellular parasite considered one of the most successful pathogens in the world, owing to its ability to produce long-lasting infections and to persist in the central nervous system (CNS) in most warm-blooded animals, including humans. This parasite has a preference to invade neurons and a ect the functioning of glial cells. This could lead to neurological and behavioral changes associated with cognitive impairment. Although several studies in humans and animal models have reported controversial results about the relationship between toxoplasmosis and the onset of dementia as a causal factor, two recent meta-analyses have shown a relative association with Alzheimer’s disease (AD). AD is characterized by amyloid- (A ) peptide accumulation, neurofibrillary tangles, and neuroinflammation. Di erent authors have found that toxoplasmosis may a ect A production in brain areas linked with memory functioning, and can induce a central immune response and neurotransmitter imbalance, which in turn, a ect the nervous system microenvironment. In contrast, other studies have revealed a reduction of A plaques and hyperphosphorylated tau protein formation in animal models, which might cause some protective e ects. The aim of this article is to summarize and review the newest data in regard to di erent pathophysiological mechanisms of cerebral toxoplasmosis and their relationship with the development of AD and cognitive impairment. All these associations should be investigated further through clinical and experimental studies.